Targeted Dysfunctionality: A Systematic Review and Conceptualization: An Abstract - Okan, Mehmet; Elmadağ, Banu (Springer International Publishing, 2019)
Nowadays, service actors are increasingly behaving offensive, destructive, and hostile with intentions to harm each other, service provision processes, the well-being of the organization, and its brand (Fisk et al. 2010; Grandey et al. 2007; Kahr et al. 2016). The skyrocketing number of negative experiences with service providers within service environments leads to more destructive and offensive hostility as a new phenomenon (Kahr et al. 2016), previously observed in intraorganizational relations (Analoui 1995). We introduce the concept of “targeted dysfunctionality” as a bridging construct that indicates “intended to harm” oriented service actor behaviors. We employed a systematic literature review of the harm-motivated dysfunctional behavior studies in both organizational behavior and marketing literatures. As a further stage of the systematic review, a meta-analytic review was conducted for testing the validity of the suggested typology in service contexts. In the systematic review, we concluded that 4 of 17 constructs (aggression, sabotage, incivility, and production deviance) can clearly explain “targeted dysfunctionality” with two dimensions (ambiguity of harm intention and humanization in service contexts). Based on these two dimensions, we defined targeted dysfunctionality as “(Un)ambiguous dysfunctional actions of service actors that are dominantly motivated by causing harm to other actors and processes in service ecosystems.” One of the main dimensions that delineate a meaningful distinction between sub-constructs is “ambiguity of harm.” Aggression and sabotage constructs have clear relations with “intent to harm” motivation, but it is hard to determine the harm motivation behind incivility and product deviance. The other dimension, which is critical to dissociate the sub-constructs, is the person-targeted/process-targeted dichotomy. Aggressive and uncivil behaviors are clearly directed at a person or a group of people (i.e., teams). On the other hand, the main goal of sabotage and production deviance behaviors is harming organizational processes (i.e., service-providing processes), rather than harming people or organizational members. In the meta-analytic review, we found significant relationships between employee-targeted dysfunctional customer behaviors (customer mistreatment) and dysfunctional employee behaviors (aggression, incivility, service sabotage, and production deviance). Supporting our typology, we found significant differences between the effect sizes of employee aggression, employee incivility, service sabotage, and production deviance. The relationship between aggression and customer mistreatment was trivial (ρ = 0.058). On the other hand, we found strong positive effects of customer mistreatment on incivility, sabotage, and production deviance in different levels (ρ = 0.403; ρ = 0.359; ρ = 0.275, respectively).